Нездійснені плани організації в Києві науково-дослідного Інституту кінематографії (1929–1931) - Росляк, Р. (Студії мистецтвознавчі, 2008)
For the Ukrainian cinematography the end of the twenties and the beginning of the thirties of the last century were the time of its rise as well as the time of unfulfilled intentions. But it made progress, in particular Kyiv picture factory was built and in 1928 it released the first film. At the beginning of the thirties a system of cinematography schools was created (it was a completion of cinematography education process). These schools trained specialists of various levels: Institute of Cinematography, two technical schools of cinematography, courses etc. But there were a lot of unsettled problems in cooperation between official instructions and creative intentions.